Forecasting sales at Ska Brewing Company - Drake, Matt (Matthew J.) (Pearson, 2014)
This new business analytics case study challenges readers to project trends and plan capacity for a fast-growing craft beer operation, so it can make the best possible decisions about expensive investments in brewing capacity. Crystallizing realistic analytical challenges faced by companies in many industries and markets, it exposes readers to the entire decision-making process, providing opportunities to perform analyses, interpret output, and recommend the best course of action. Author: Eric Huggins, Fort Lewis College.